A multi-shape hybrid symmetric encryption algorithm to thwart attacks based on the knowledge of the used cryptographic suite - Altigani, Abdelrahman (Elsevier Ltd, 2019)
This research paper introduces a novel symmetric encryption algorithm that provides the confidentiality security service without leaking enough information about the exact encryption algorithm or other cryptographic parameters to anyone except the legitimate receiver. This is achieved by utilizing a set of sound existing symmetric encryption algorithms, namely, the Advanced Encryption Standard,MARS,RC6, Serpent and Twofish. The identity of the algorithm used to secure the current message, along with other cryptographic parameters (e.g. mode of operation, key length), are hidden from anyone except the legitimate receiver. These parameters are shared securely between communicating parties by utilizing some of the symmetric key bits. The cipher suite in addition to the encryption key, changes systematically and securely with every new message, leaving the opponent with no enough information to launch any effective attack. The algorithm performance is tested, and the overall performance is close to the performance of conventional encryption with a delay of about 16.52 CPU Cycles per message. From a security point of view, the possibility of cryptanalysis is diminished significantly, as no party except communicating parties has any knowledge of the cryptographic parameters in use.